ION-CHROMATOGRAPHIC DETERMINATION OF IONS IN BIODIESEL, BIOETHANOL AND BIOGAS - Ljubiša Ignjatović; Ivana Sredović Ignjatović (Journal of Engineering & Processing Management, 2015)
The reduction of the greenhouse gas emissions and the assessment of renewable energy sources are among today's most challenging tasks. In this context biofuels have emerged as promising alternatives. Successful commercialization and market acceptance of biofuels are dependent on the presence of ions that induce negative impact on the vehicle components and on the environment. In this context ion chromatography (IC) plays a decisive role. Besides the quantitation of cations, glycerol and antioxidants in biodiesel, a direct-injection IC method allows the determination of the chloride and sulfate content in bioethanol and has become an invaluable tool for the process control and monitoring of biogas reactor samples. This work provides an use of IC methods combined with inline sample preparation for the determination of anions and cations in organic biofuels and volatile organic acids in process solutions: Traces of anions in a gasoline/ethanol blend can be determined in the ppb range after matrix elimination; Alkali metals and water-extractable alkaline earth metals in biodiesel are determined after extraction with nitric acid and subsequent dialysis; In biogas reactor samples, low-molecular-weight organic acids stem from the biodegradation of organic matter can be determined applying ion exclusion chromatography after dialysis or ultrafiltration.
Keywords: biodiesel; bioethanol; biogas; ion chromatography